2021
DOI: 10.3390/nu13041212
|View full text |Cite
|
Sign up to set email alerts
|

The Anticancer Effects of Flavonoids through miRNAs Modulations in Triple-Negative Breast Cancer

Abstract: Triple- negative breast cancer (TNBC) incidence rate has regularly risen over the last decades and is expected to increase in the future. Finding novel treatment options with minimum or no toxicity is of great importance in treating or preventing TNBC. Flavonoids are new attractive molecules that might fulfill this promising therapeutic option. Flavonoids have shown many biological activities, including antioxidant, anti-inflammatory, and anticancer effects. In addition to their anticancer effects by arresting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 40 publications
(25 citation statements)
references
References 353 publications
(358 reference statements)
0
25
0
Order By: Relevance
“…TQ has been studied in in vitro and in vivo models for its antioxidant, anti-inflammatory, and anti-cancer properties [ 19 ]. Recently, myriads of research demonstrated the anticancer effect of TQ on several types of cancer, including breast, ovarian, larynx, colon, myeloblastic leukemia, osteosarcoma, and lung cancer [ 20 , 21 ]. Anti-proliferation, apoptosis induction, cell cycle arrest, and anti-metastasis/anti-angiogenesis are crucial mechanisms employed by TQ against cancer [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…TQ has been studied in in vitro and in vivo models for its antioxidant, anti-inflammatory, and anti-cancer properties [ 19 ]. Recently, myriads of research demonstrated the anticancer effect of TQ on several types of cancer, including breast, ovarian, larynx, colon, myeloblastic leukemia, osteosarcoma, and lung cancer [ 20 , 21 ]. Anti-proliferation, apoptosis induction, cell cycle arrest, and anti-metastasis/anti-angiogenesis are crucial mechanisms employed by TQ against cancer [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Autophagy is a process found in low levels under normal conditions known as self-eating, which maintains cellular homeostasis balancing catabolic mechanisms. Autophagy is controlled by numerous pathways targeting multiple disease states, including viral and bacterial infections, cancer, diabetes, and neurodegenerative diseases [ 146 ]. It is activated in response to stress to remove excess damaging cellular proteins and organelles.…”
Section: Flavonoidsmentioning
confidence: 99%
“…It is activated in response to stress to remove excess damaging cellular proteins and organelles. Autophagy comprises five key steps: induction, nucleation, vesicle lengthening and maturation, vesicle fusion, and degradation and recycling [ 146 ]. These processes are regulated by the recruitment of autophagy-related protein repressed by the mechanistic target of rapamycin complex 1 [ 146 ].…”
Section: Flavonoidsmentioning
confidence: 99%
“…The ability of flavonoids to affect miRNAs involved in carcinogenesis (review, [ 135 , 136 ]) is particularly relevant in CSCs. Thus, in breast cancer cells, exposure to Glabridin, a phytochemical from the root of Glycyrrhiza glabra, upregulated miR-148a via promoter de-methylation, leading to the suppression of SMAD2 and decrease in CSC-like properties [ 137 ].…”
Section: Anti-csc Activity Of Flavonoids Mediated By Modulation Of Micrornasmentioning
confidence: 99%